2009
DOI: 10.1167/iovs.08-2743
|View full text |Cite
|
Sign up to set email alerts
|

The Vacuolar-ATPase Complex Regulates Retinoblast Proliferation and Survival, Photoreceptor Morphogenesis, and Pigmentation in the Zebrafish Eye

Abstract: These results demonstrate that the v-ATPase complex plays several critical roles during vertebrate eye development and maintenance, and they suggest that defects in v-ATPase complex function could possibly underlie human ocular disorders that affect the RPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 65 publications
8
106
0
Order By: Relevance
“…We designed translational blocking and splice-blocking morpholinos to both the Vod1 and V1D subunits of V-ATPase. Injection of embryos with these morpholinos consistently resulted in the hypopigmentation phenotype as reported [28] (Figure 5B), confirming the efficacies of these morpholinos. The heart looping was randomized in the Vod1 morphants ( Figure 5C), consistent with a previous report that inhibition of VATPase by chemical inhibitors induces left-right patterning defects in zebrafish [29].…”
Section: V-atpase Regulates Ciliogenesis In Multiple Organs In Zebrafishsupporting
confidence: 72%
“…We designed translational blocking and splice-blocking morpholinos to both the Vod1 and V1D subunits of V-ATPase. Injection of embryos with these morpholinos consistently resulted in the hypopigmentation phenotype as reported [28] (Figure 5B), confirming the efficacies of these morpholinos. The heart looping was randomized in the Vod1 morphants ( Figure 5C), consistent with a previous report that inhibition of VATPase by chemical inhibitors induces left-right patterning defects in zebrafish [29].…”
Section: V-atpase Regulates Ciliogenesis In Multiple Organs In Zebrafishsupporting
confidence: 72%
“…In contrast to the expression pattern of atp6v0c, which has been shown to be expressed in the retinal pigment epithelium and ganglion cells in the eye, the telencephalon, and the pigment cells and mucous cells of the fish body (Wang et al, 2008;Nuckels et al, 2009), atp6v0c2 is expressed specifically in the developing nervous system (Fig. 2).…”
Section: Atp6v0c2 Is Specifically Expressed In the Zebrafish Cnsmentioning
confidence: 90%
“…A recent study reported that apt6v0c mutant zebrafish were microphthalmic, and their eyes possessed a thin, hypopigmented retinal pigmented epithelium (RPE) (Nuckels et al, 2009). BrdU incorporation experiments and TUNEL staining revealed that apt6v0c function was essential for the exit of retinoblasts from the cell cycle, as well as for the sustained proliferation of retinal stem cells (Nuckels et al, 2009).…”
Section: Atp6v0c2 Function Is Dispensable For Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations